Multitracer extension of the halo model: probing quenching and conformity in eBOSS. Issue 1 (8th July 2020) - Alam, Shadab; Peacock, John A; Kraljic, Katarina; Ross, Ashley J; Comparat, Johan
ABSTRACT: We develop a new Multitracer Halo Occupation Distribution (MTHOD ) framework for the galaxy distribution and apply it to the extended Baryon Oscillation Spectroscopic Survey (eBOSS) final data between z = 0.7 − 1.1. We obtain a best fitting MTHOD for each tracer and describe the host halo properties of these galaxies. The mean halo masses for LRGs, ELGs, and QSOs are found to be $1.9 × 10^{13} \, h^{-1}M_\odot$, $1.1 × 10^{12} \, h^{-1}M_\odot$, and $5 × 10^{12} \, h^{-1}M_\odot$ respectively in the eBOSS data. We use the MTHOD framework to create mock galaxy catalogues and predict auto- and cross-correlation functions for all the tracers. Comparing these results with data, we investigate galactic conformity, the phenomenon whereby the properties of neighbouring galaxies are mutually correlated in a manner that is not captured by the basic halo model. We detect 1-halo conformity at more than 3σ statistical significance, while obtaining upper limits on 2-halo conformity. We also look at the environmental dependence of the galaxy quenching efficiency and find that halo mass driven quenching successfully explains the behaviour in high density regions, but it fails to describe the quenching efficiency in low density regions. In particular, we show that the quenching efficiency in low density filaments is higher in the observed data, as compared to the prediction of the MTHOD with halo mass driven quenching. The mock galaxy catalogue constructed in this paper is publicly available on this website 1 .